The Effect of Maternal Obesity on Fetal Macrosomia: Meta-Analysis - Kumalasari, Vilia Ayu; Murti, Bhisma; Adriani, Rita Benya (Journal of Maternal and Child Health, 2023)
Background: Obesity is a condition that shows an imbalance between height and weight. Obesity in women poses a risk to future pregnancies and their pregnancy outcomes. One of the risks of pregnancy in obese women is the birth of babies with excess weight or macrosomia. Excess birth weight can increase the risk of death for both mother and baby. This study aims to examine the effect of obesity in pregnant women on child birth using macrosomia. Subjects and Method: Meta-analysis was performed with the PRISMA flowchart using PubMed, Science Direct, and Google Schoolar databases. Keywords used ((maternal obesity OR obesity in pregnancy) AND (macrosomia OR large for gestational)). There were 11 studies with a cohort design published in 2012-2022 that met the inclusion criteria. Analysis was performed using Revman 5.3.Results: There were 11 articles originating from three continents, namely Asia (2 studies from China, 2 from Saudi Arabia, 1 from Taiwan), the Americas (3 from the United States, 1 from Brazil), and the European continent (1 from Poland and 1 from Spanish). The heterogeneity of effect estimates between primary studies showed I² = 95% (p<0.001), so the analysis used the Random Effect Model (REM). Obese pregnant women had a 2.03 times risk of having a baby with macrosomia compared to pregnant women without obesity (aOR=2.03, 95% CI=1.88 to 2.18; p<0.001).Conclusion: Obesity in pregnant women increases the risk of having a baby with macrosomia. Keywords: maternal obesity, macrosomia. Correspondence: Vilia Ayu Kumalasari. Master's Program in Public Health, Universitas Sebelas Maret. Graduate School Building Universitas Sebelas Maret, Jalan Ir. Sutami 36 A, Surakarta, Jawa Tengah, 57126. Email: villia.kumalasari@gmail.com Mobile: 082140814930.